How We Move Beyond a Policy Prescription to Action - Moriah Ellen and Judith Shamian (HealthcarePapers, 2011)
In response to "Evidence-Based Policy Prescription for an Aging Population," by Chappell and Hollander, this paper proposes that efforts be made to execute strategies to build the political momentum and public support necessary for concrete action toward achieving the recommended policies. It also suggests the implementation of knowledge translation strategies to assist in disseminating and integrating existing successful programs across the wider health system. Finally, this paper proposes a concerted and robust mobilization of forces in order to move from evidence-based agenda setting into active policy implementation. A key element of this transition involves placing greater emphasis on interest group activation and public policy deliberation. Such a focus would enable consensus between policy makers, decision-makers, interest groups and the public, garnering the political traction necessary to allow for the implementation of healthy public policy that best serves the needs of an aging population.
Keywords: Aging, public policy, sustainable healthcare system, elderly, healthcare reform, geriatrics